INVESTIGATING CCTV BREACHES: THE MIRNA SALIHIN DEATH CASE (COFFEE CYANIDE) - Ahmad Fahrudi Setiawan; Suryo Adi Wibowo; Akbar Bimantara Trahestiawan (Computer Science Department, Malang National Institute of Technology, 2024)
The death of Mirna Salihin in 2016, allegedly caused by cyanide poisoning in a cup of iced coffee, shocked Indonesia and raised significant questions about the integrity of digital evidence in criminal investigations. One of the key pieces of evidence in this case was the CCTV footage from a café, which was critical in establishing the sequence of events leading to Mirna's death. However, the investigation was complicated by the breach and manipulation of the CCTV data, leading to concerns about the authenticity and reliability of digital evidence in criminal trials. This paper explores the role of CCTV footage in criminal investigations, specifically in the context of the Mirna Salihin case. We analyze how the breach of digital evidence impacted the investigation, the challenges associated with preserving and verifying CCTV footage, and the implications for the legal admissibility of digital evidence. Additionally, we discuss the importance of ensuring the integrity of surveillance systems and the ethical and legal frameworks that govern the collection and handling of digital evidence. By examining this case, the paper highlights the critical need for robust digital forensic practices and transparency in the handling of digital evidence, especially in high-profile criminal cases where the stakes are high